Os desafios do Ministério Público do Trabalho na defesa do direito social ao trabalho de migrantes - Ferreira, Januário Justino (2018)
The present study goal is to discuss the employability in Brazil, in the midst of the intense foreign migratory process and the nearby 14 million brazilians unemployed. All discussions are focused in aspects of the fundamental principle of social labor law and tax incentives as result of public policies, particularly for the productive sectors that has been benefit from tax releases and do not return jobs and benefits to society as counterparts rents promised. The importance of the discussions can be seen from the large amounts of almost R$ 284.84 billion granted in recent years by the Federal Government to encourage the productive sectors, including as discharge in payroll to justify job generation, but it was not even able to maintain the existing jobs, given the unemployment increase in proportionally to the increase of the public resources spent in the renunciation of taxes. This is an important issue because not even the government is able to measure these amounts or the effectiveness of the incentives granted, allowing this inefficiency to capture public resources without reaching society interests like health, education, safety, as well as employment and income. One of the points studied is the migration to Brazilian territory, its consequences in constitutional and infraconstitutional guarantees, such as the guarantee of citizenship work, observing the nationality of work. It also has been studied the numbers of tax incentives and the inefficiency of their policies, as well as the intervention of the Public Power in the private economy so it can help generate jobs, including jobs for immigrants, and the action by the Public Labor Ministry in the productive sectors that neglect the creation and maintenance of promised jobs in the concessions of tax incentives. Economic theory is also addressed in aspects such as behavioral theory, rationality, market failure and balance, cost-effectiveness, as well as basic principles of the Democratic State of Law, such as the principles of human dignity, values of labor, equality and economy, all of which must be considered in the process of state intervention for the generation of jobs and incomes.